THE INTERNATIONAL CONGRESS ON ACCOUNTING. - Littleton, A. C.; Morey, lloyd; Himmelblau, David; Ross, F. E. (The Accounting Review, 1929)
Abstract One of the greatest events in accounting history was the International Congress on Accounting, held in New York during the week of September 9, 1929. Despite the variation in laws governing accountancy and in the forms in which accounting practice is conducts, a remarkable unanimity was recognized by everybody as existing in the problems faced by the profession throughout the world. There are two views rather definitely set professional auditing over against social economics; they contrast shareholder's desire for information concerning the remainders of original investments with managers' desires for information concerning the intricate details of profit making. To apply reproduction costs to the balance sheet would place the statement, therefore, in conflict with prudence and the sound principle of realized profit only. But on the other hand, the author points out, to apply only past costs in cost accounting would be to deprive the management of current information very necessary to proper market judgment, for competition is going to be most felt from those who most recently bought in the market and thus have secured a tangible new base for their pricing policy.